Penataan Materi Muatan Peraturan Pemerintah dan Peraturan Presiden dalam Sistem Hukum Indonesia - Hadinatha, Miftah Faried (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2022)
This article was written departing from the unrest of the condition of the laws and regulations in Indonesia experiencing hyper-regulation. This is one of them is due to so often the material of Government Regulations (PP) and Presidential Regulations (Perpres) delegate technical rules to lower regulations, such as Ministerial Regulations. In that case, the study seeks to decide for both types of regulations. The question will be focused in two; First how to organize the content material pp and perpres? Second, what are the implications that arise from the arrangement of PP and Perpres charge material? This type of research is normative with secondary data being its main base. While the approach used is conceptual and legislation. The first research results, the arrangement of PP and Perpres materials are carried out by first complying with the concept of hieraricis, then making the type of two, then ensuring the style of sentence formulation, continued to adhere to the principles of the formation of laws and regulations that are all contained in academic manuscripts, and ended with the omnibus law method. Second, the implications that occur as a result of the arrangement is that the centralization of the issuance of regulations will be on the President, the rules in question will be easily supervised by the President, and minimize the symptoms of sub-delegations.